PRAGMATISME DALAM PENERAPAN METODE LEARNING BY DOING DENGAN MEDIA PUZZLE PADA MATERI IPAS: ANALISIS JURNAL SINTA 4 SAMPAI 6 - Mirna Astuti; Maemonah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning that tends to be monotonous can hinder the achievement of the learning process and impact on learning outcomes and goals that are not maximized. In learning, students tend to get bored easily and are easily distracted by things that attract their attention, which makes the learning process not conducive. Efforts that can be made to attract students' attention to the learning process are through the learning by doing method with Puzzle media to create a pleasant learning atmosphere that will be seen from the perspective of pragmatism philosophy. This research was conducted by looking at related literacy related to the research conducted, the sources used were only limited to sinta 3-5 with the aim of maintaining the efficiency and accuracy of the data. The results of this study state that learning becomes fun for students with the first indicator that students feel that learning is like playing, Puzzle media that makes students interested in particIPAting in learning.